PENERAPAN KINERJA DENGAN PENDEKATAN BALANCED SCORECARD PADA PT POS INDONESIA CABANG KUTACANE - Desi Aramana (Jurnal Akuntansi dan Keuangan, 2020)
The purpose of this study was to determine how the application of financial performance with the balanced scorecard approach at PT Pos Indonesia Kutacane. This research uses descriptive methods with qualitative data and quantitative data. Data analysis techniques were performed using validity and reliability tests, by looking at fact data from the company based on each perspective-perspective contained in the belenced scorecard, namely: financial perspective, customer perspective, internal business process perspective, and growth perspective and learning. The results of the study at PT Pos Indonesia Kutacane Branch showed that financial performance showed poor conditions in the period 2016 to 2018 as measured by the ratio used, the performance of the customer perspective had done various things to provide good service to customers, the performance of the process perspective Internal business which includes innovation and observation of employees shows good results, and performance on the growth perspective and lessons from observations of employee capability and employee satisfaction show good results.